2
$\begingroup$

How does one prove that the unique continuous distribution with the memoryless property is the exponential distribution? i.e. Suppose we know that a continuous random variable $X$ satisfies

$$P\{X > t+s \mid X > s \} = P\{X > t \}$$

Then how do we show that $X \sim \text{Exponential}(\lambda)$ for some $\lambda > 0$?

Thanks.

$\endgroup$
  • 1
    $\begingroup$ This is equivalent to $P(X>t+s)=P(X>t)P(X>s)$ which tells you that $P(X>t)$ is a decaying exponential. $\endgroup$ – A.S. Feb 20 '16 at 16:30
  • $\begingroup$ I always find it irritating when someone writes $\text{Exponential}(\lambda)$ as if that were not at best ambiguous. Sometimes $X\sim\text{Exponential}(\lambda)$ means $\Pr(X>x) = e^{-\lambda x}$ for $x\ge0$ (so the intensity is $\lambda$ and the expected value is $1/\lambda$) and sometimes it means $\Pr(X>x) = e^{-x/\lambda}$ for $x\ge0$ (so the intensity is $1/\lambda$ and the expected value is $\lambda$). $\qquad$ $\endgroup$ – Michael Hardy Feb 20 '16 at 17:12
  • $\begingroup$ @Michael I shared your sentiment initially, but it looks like today - esp. in modern works - $\lambda$ is predominantly/exclusively referring to rate/intensity while $\beta$ is to denote the mean - but it might be field/application dependent. $\endgroup$ – A.S. Feb 21 '16 at 3:21
  • $\begingroup$ math.stackexchange.com/questions/1801830/… $\endgroup$ – StubbornAtom Dec 6 '19 at 9:44
4
$\begingroup$

Let $g(t) = \Pr(X>t)$. Then memoryless tells us that $g(t+s)=g(t)g(s)$. Consequently $g(t_1+t_2+t_3)=g((t_1+t_2)+t_3) = g(t_1+t_2) g(t_3) = g(t_1) g(t_2) g(t_3)$, and it should become clear why $g(t_1+\cdots+t_n)=g(t_1)\cdots g(t_n)$ for every finite number $n$. Thus $$ g(n) = g(1+\cdots+1) = g(1)\cdots g(1) = (g(1))^n, $$ so $g$ is an exponential function of $n$ as long as $n$ is a positive integer. So what about non-integers? $$ \left(g\left(\frac 1 8 \right)\right)^8 = g\left(\frac 1 8\right)\cdots g\left(\frac 1 8\right) = g\left(\frac 1 8 + \cdots + \frac 1 8 \right) = g(1) $$ so $$ g(1)^{1/8} = g\left(\frac 1 8 \right) $$ and it becomes clear why $g(t)=g(1)^t$ if $t=\left\{1\text{ over a positive integer}\right\}$. Next let's try $11/8$: \begin{align} g\left(\frac{11}8\right) & = g\left( \frac 1 8 + \cdots + \frac 1 8 \right) \\[10pt] & = \left(g\left(\frac 1 8 \right)\right)^{11} & & \text{because of what was shown about integers above} \\[10pt] & = \left( g(1)^{1/8} \right)^{11} & & \text{because of what was shown about $1/8$ above} \\[10pt] & = (g(1))^{11/8}, \end{align} so $g(t)$ behaves like an exponential function with base $g(1)$ when $t$ is a positive rational number.

Finally, what about irrational numbers $t$? Notice that $g(t) = \Pr(X>t)$ is squeezed between $\Pr(X>a)$ for all positive rational numbers $a$ that are $>t$ and $\Pr(X>b)$ for all positive rational numbers $b$ that are $<t$. And also $g(1)^t$ is squeezed between all numbers $g(1)^a$ for rational numbers $a$ that are $>t$ and all numbers $g(1)^b$ for rational numbers $b$ that are $<t$. One can deduce then that $g(t)$ is still equal to $g(1)^t$.

Hence we have $$ g(t) = g(1)^t \text{ for all real }t\ge0. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.